2014
DOI: 10.1016/j.chb.2013.10.036
|View full text |Cite
|
Sign up to set email alerts
|

Cyberbullying on social network sites. An experimental study into bystanders’ behavioural intentions to help the victim or reinforce the bully

Abstract: Cyberbullying on social network sites : an experimental study into bystanders' behavioral intentions to help the victim or reinforce the bully

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
210
3
19

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 282 publications
(246 citation statements)
references
References 39 publications
14
210
3
19
Order By: Relevance
“…The observer's role differs greatly depending on the severity of the incident, as indicated by Bastiaensens et al (2014). These authors found that participants who were exposed to the more severe harassing incident, had significantly higher behavioral intentions to help the victim.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…The observer's role differs greatly depending on the severity of the incident, as indicated by Bastiaensens et al (2014). These authors found that participants who were exposed to the more severe harassing incident, had significantly higher behavioral intentions to help the victim.…”
Section: Discussionmentioning
confidence: 77%
“…On the other hand, when the cyberbullying incident was considered less severe, observers could perceive a smaller opportunity to gain social rewards. Additionally, the presence of other bystanders could cause a perceived risk for negative social evaluation when helping (Bastiaensens et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been used to determine the users' personality [26,18], to detect the most influential users [35], or to understand how information flows [36]. Social network analysis has also been applied to social contexts such as terrorism [34] and cyberbullying [3].…”
Section: Introductionmentioning
confidence: 99%